A formação do professor de língua inglesa e a legislação : o caso do curso de Letras habilitação Português-Inglês da UFS - Nascimento, Laudo Natel do (2010)
This study analyzes the initial training education for Language teachers, especially when it comes to English language teaching, considering the legislation which gives it support. The Portuguese-English course offered by the Federal University of Sergipe was chosen as the empirical field of this research, and its main document, the pedagogical project (Resolution n.59/2007/CONEPE), was analyzed. It is a qualitative research of a critical-descriptive type. The dialectic method was used for deepening the analysis of theories based on bibliographical and documental research. During the investigation, the social, economic, political, and educational contexts were analyzed, taking into account the changes in Capitalism according to Netto and Braz (2006), Bolaño (2002), Behring, and Boschetti (2006), among others. University education in this context of changes was also analyzed, taking into consideration the contributions by Sguissardi (2006), Chauí (2003), and Nascimento et al (2006), as the local context (Sergipe) was considered. The initial training education for teachers was also studied. First, in a wider way, referring to the public policies for teachers training based on studies by Weber (2002), Dourado (2001, 2002), and Freitas (2002); and some documents, such as the National Educational Law (lei 9.394/1996) and the National Policies for the Initial Training of Teachers of Basic Education at the University Level (Resolution CNE/CP 1, February 18th, 2002). Teachers training for English teachers, which is the focus of this study, was also examined. In this sense, a dialogue was established, involving the subject of Resolution n.59/2007/CONEPE, which approves the Political and Pedagogical Project of the Portuguese-English Course at UFS, the theoretical information of several authors, such as Almeida Filho (2007) and Paiva (2003), as well as the legislation which deals with the teaching of English and teachers training education for English teachers. As far as the legislation is concerned, the main documents consulted were: the National Curricular Parameters for Foreign Language, Elementary and Secondary Education, the Curricular Orientation for Secondary Education, and the Curricular Policies for Language Courses. The dialogue established points to the fact that the university, especially the teachers training course designed for English teachers, has followed the idea of providing a service but not of producing knowledge, whereas this last one should be its main objective. In this sense, the analysis showed as main problems concerning teachers training that are offered to English teachers who attend the course in study: the reduced number of hours dedicated to the teaching of the English language, as well as the insufficient number of hours directed to teachers training education.